Review of oil shale in-situ conversion technology. (1st July 2020) - Kang, Zhiqin; Zhao, Yangsheng; Yang, Dong
Highlights: The progress of oil shale in-situ conversion technology is reviewed extensively. Pores/fractures formed in oil shale pyrolysis constitute a channel for fluid flow. Oil shale in-situ steam injection technology is proposed. The principles of effective pyrolysis energy of oil shale are proposed. Abstract: Oil shale is an important strategic resource with tremendous reserve. In-situ retorting is the only technology available to achieve large-scale industrial exploitation. This paper systematically introduces the intensive researches conducted by Zhao's team on oil shale retorting, as well as the progress of oil shale in-situ conversion technology in the world. The oil shale deposit in sedimentary strata with hidden layering, and the kerogen in oil shale is dispersed in flat strips that ranges from a few to tens of microns in size. A large amount of micro-scale pores and fractures are formed along the bedding in oil shale during the in-situ pyrolysis process, which creates connected channels and enhances the effectiveness of thermal fluid injection and the yield of pyrolysis products. Back to 2005, Zhao's team invented the oil shale in-situ retorting technology by injecting superheated steam, and related technical advantages are analyzed in detail. The principles of effective pyrolysis energy of oil shale are proposed so as to evaluate development stage of the reserve, meantime, the advantages of steam as a heat carrier fluid are specified by comparing the effective injection energy of steam and other gases. Furthermore, the scientific, technical, industrial advances of latest developments, including electric heating, fluid injection heating, combustion, and radiant heating in oil shale in-situ conversion technology are reviewed in detail. By comparing with the advantages and disadvantages of various technical solutions, the directions in which several key problems should be solved were pointed out.